The Researchers Have Left the Building: What Contributes to Sustaining School‐Based Interventions Following the Conclusion of Formal Research Support?. (May 2014) - Friend, Sarah; Flattum, Colleen F.; Simpson, Danielle; Nederhoff, Dawn M.; Neumark‐Sztainer, Dianne
ABSTRACT BACKGROUND This study examined the sustainability of New Moves, a school‐based program aimed at decreasing weight‐related problems in adolescent girls. The National Cancer Institute recognizes New Moves as a research‐tested intervention program that produced positive behavioral and psychosocial outcomes. METHODS Ten schools participated in the sustainability study. Teachers completed a survey and interview, and research staff observed 1 physical education (PE) class within 2 years of the study's completion. Qualitative data were grouped by themes. Frequencies were calculated using quantitative data. RESULTS All schools continued all‐girls PE classes using New Moves components following the study period. Fewer schools continued the nutrition and social support classroom modules and individual coaching sessions while no schools continued lunch get‐togethers. Program components were sustained in both New Moves intervention schools and control schools. CONCLUSIONS Programs are most likely to be sustained if they (1) fit into the current school structure, (2) receive buy‐in by teachers, and (3) require minimal additional funds or staff time. Providing control schools with minimal training and intervention resources was sufficient to continue program components if staff perceived the program was important for students' health and compatible within the school's existing infrastructure.